2007
DOI: 10.1002/crat.200710991
|View full text |Cite
|
Sign up to set email alerts
|

Shape‐controlled synthesis of ZnO architectures

Abstract: Several ZnO nanoarchitectures have been selectively prepared through hydrothermal method including urchin-shaped, flower-shaped, butterfly-shaped, and cacti-shaped microstructures. The influence of reaction temperature and the concentration of amphiphilic copolymer on the morphologies and shapes of ZnO samples have been studied. The samples were characterized using XRD, TEM, and SEM. It was found that ZnO nanorods or their assemblies were fabricated at higher temperature, whereas ZnO nanosheet architectures we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…This behavior might indicate that some surface spin structures such as canted spin structures or spin-glass structures start to occur with increasing the Cr concentration above a certain value. The synthesizing method of the nanoparticles is known to produce different surface structures and magnetic properties [28][29][30].…”
Section: Resultsmentioning
confidence: 99%
“…This behavior might indicate that some surface spin structures such as canted spin structures or spin-glass structures start to occur with increasing the Cr concentration above a certain value. The synthesizing method of the nanoparticles is known to produce different surface structures and magnetic properties [28][29][30].…”
Section: Resultsmentioning
confidence: 99%
“…So far, a variety of Zn nanostructures such as nanowires, nanorods, nanodots, nanotubes, nanosheets, nanobelts, nanoribbons, nanorings, nanoaeroplanes, nanocombs, nanobridges and nanonails have been synthesized via various physical and chemical fabrication techniques [10][11][12][13][14][15]. These methods include vapor phase transport process, chemical vapor deposition, thermal evaporation process, electrodeposition, hydrothermal, self-assembly, and template-assisted sol-gel process [16][17][18][19][20][21]. The vapor methods usually involve sophisticated equipments, complex procedures or rigid experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic properties of ferrite nano-powders SrFe 12-x R x O 19 were found [35] to depend on the heat treatment conditions (temperature and time). In another study, the synthesizing method was found to determine the shapes (and accordingly the surface disorder) of the ZnO nanostructures [36]. Thus the synthesizing method of the nanoparticles has influence on their microstructure and shape which leads to changes in core and surface magnetic properties.…”
Section: Methodsmentioning
confidence: 98%